(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Rocks are characterized in supralittoral zone of the Crimean coast of the Black and Azov Seas. The article presents data on the species list of Cyanophyta in various supralittoral rocky substrates.